Effects of anticoagulant and antiplatelet agents in severe traumatic brain injury in an asian population – A matched case-control study. (December 2019) - Qiu, Liming; Han, Julian Xinguang; See, Angela An Qi; King, Nicolas Kon Kam
Highlights: The use of ACAP in severe TBI did not affect mortality outcome at 14 days or 6 months. Functional outcomes at 6 months were similar using a sliding dichotomy approach. This is the only study that investigated exclusively the effects of ACAP use in severe TBI. Abstract: The use of anticoagulation and antiplatelet agents (ACAP) has steadily increased over recent years. However, the effects of ACAP on traumatic brain injuries (TBI) are not well investigated. The aim of this study was to investigate the effects of pre-injury ACAP use on clinical outcome and mortality in severe TBI. A retrospective case-control study was performed for all patients who presented with severe TBI (GCS < 8) to the National Neuroscience Institute, Singapore, between 2006 and 2009. Patients with pre-injury ACAP use were compared to matched controls. Outcome measures were mortality at 14 days and 6 months, and Glasgow Outcome Score (GOS) at 6 months using a sliding dichotomy approach. Univariate analysis was performed using Chi-square and student's t -test and logistic regression was used to model the effect of ACAP on mortality rate. Forty-five patients with pre-injury use of ACAP were compared with matched controls. The mortality at 14 days (OR = 0.5, 95% CI 0.2–1.4) and 6 months (OR = 0.7, 95% CI 0.2–1.9) were not significantly different between the 2 groups. Using the sliding dichotomy approach, there was no difference in the odds for unfavorable functional outcomes at 6 months (OR = 1.2, 95% CI 0.4–3.7). In this case-control study, the use of ACAP did not have a significant effect on mortality and adverse outcomes in patients with severe TBI. This would suggest that in severe TBI, ACAP use may not contribute significantly to the overall prognosis.